Novel, Low-cost Ear Elevation Splint for Auricular Construction - Emily S. Chwa, MD; Breanna Baltrusch, CPO, LPO; Erin Claussen, CO, LO; Sophia Allison, BA; Nikhil D. Shah, MD; Akira Yamada, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Modern approaches to autogenous auricular reconstruction involve a multistage approach where ear elevation is an independent procedure. The goal is to project the reconstructed ear at an anatomically accurate and symmetric auriculocephalic angle, but postoperative scar contraction may adversely affect the long-term outcomes. An ear elevation splint was developed to provide rigid support for the auricle during the acute healing period to promote lasting elevation. The splint is low cost, made from commonly used orthotic materials, and can be conveniently customized for each patient in less than 15 minutes.